Metode Pembelajaran Pendidikan Agama Islam Di Masa Pandemi COVID 19 - Arifin, Zaenal (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Learning is the process of students interacting with educators and learning resources in a learning environment in order to acquire knowledge, master skills and character, and develop a trusting attitude in students. During the COVID-19 pandemic, the distance learning process (PJJ) agreed upon to break the chain of COVID-19 spread requires collaboration between existing methods while adhering to the PJJ system teaching method's principles. Circular Letter No. 4 of 2020 from the Minister of Education and Culture recommends that all activities in educational institutions be kept at a distance and that all material submissions be made at the students' respective homes. During the Covid-19 pandemic, the following learning methods may be used: 1) Project-Based Learning, 2) Online Learning, 3) Offline Learning, 4) Home Visit Learning, 5) Integrated Curriculum, 6) Blended Learning, and 7) Radio Learning.Keywords: Islamic Education; Covid 19 Pandemic Period AbstrakPembelajaran merupakan proses interaksi peserta didik dengan pendidik dan sumber belajar pada suatu lingkungan belajar, agar dapat terjadi proses perolehan ilmu pengetahuan, penguasaan kemahiran dan tabiat, serta pembentukan sikap kepercayaan pada peserta didik. Pada masa pandemi covid 19 proses pembelajaran jarak jauh (PJJ) yang telah disepakati untuk memutus mata rantai meluasnya covid 19 diperlukan adanya kolaborasi atara metode yang ada dengan tetap memperhatikan prinsip-prinsip metode mengajar sistem PJJ. Surat Edaran nomor 4 tahun 2020 dari Menteri Pendidikan dan kebudayaan yang menganjurkan seluruh kegiatan di institusi pendidikan harus jaga jarak dan seluruh penyampaian materi akan disampaikan di rumah masing-masing. Metode pembelajaran yang dapat dipakai pada masa Pandemi Covid 19, diantaranya; 1) Project Based Learning, 2) Daring Method, 3. Luring Method, 4. Home Visit Method, 5. Integrated Curriculum, 6. Blended Learning, 7. Pembelajaran melalui RadioKata Kunci: Pendidikan Islam; Masa Pandemi Covid 19